Pengaruh Model Problem Based Leraning Terhadap Hasil Belajar Siswa Kelas VIII SMP Pada Materi Teorema Pythagoras - Ai Nursipa; Devi Nurul Yuspriyati (Departement of Mathematics Education, 2019)
The background of this research is that the situation in the field shows that the pythagorean theorem material is an abstract material, complicated, and requires precision in calculating using formulas. The purpose of this study is for learning learning using the PBL model (Problem Based Learning) in the Pythagoras theorem material. The method of this study used the exeriment method with the design of the pretest-posttest group, the subject of this study was class VIII of SMP Negeri 2 Campaka Mulya which produced 32 students consisting of 20 males and 12 females. The instruments used are tests and non-tests. Data collection tools are RPP Learning Implementation Plans, Observation Sheets, and Test Sheets. Based on the results of class VIII tests before using the PBL model in pythagoras lotus material obtained an average value of 53. And the results of class VIII tests after using the PBL model on pythagoras teorema material scored an average value of 75. and after the application of the PBL model Based on teacher observation and students in the implementation of mathematical learning in the material of the pyhtagorean theorem can be concluded to run well. 78% and 75% student activities are carried out.